2006
DOI: 10.1007/s10278-006-0860-9
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Contours of Breast Masses in Mammograms

Abstract: Fractal analysis has been shown to be useful in image processing for characterizing shape and gray-scale complexity. Breast masses present shape and gray-scale characteristics that vary between benign masses and malignant tumors in mammograms. Limited studies have been conducted on the application of fractal analysis specifically for classifying breast masses based on shape. The fractal dimension of the contour of a mass may be computed either directly from the 2-dimensional (2D) contour or from a 1-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 37 publications
(6 reference statements)
2
122
0
7
Order By: Relevance
“…Other boundary features applied in medical image analysis include the normalized radial length (NRG) [19], the area ratio [20], the fractal dimension (FD) [21], [31], the roughness index, the spiculation index, and the fractional concavity [23]. In addition, the extraction of boundary features by analyzing spectral domain, as it is the case with Fourier descriptor or wavelet descriptor, has been proved to provide noise-robust boundary representation in various applications [31].…”
Section: Boundary Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Other boundary features applied in medical image analysis include the normalized radial length (NRG) [19], the area ratio [20], the fractal dimension (FD) [21], [31], the roughness index, the spiculation index, and the fractional concavity [23]. In addition, the extraction of boundary features by analyzing spectral domain, as it is the case with Fourier descriptor or wavelet descriptor, has been proved to provide noise-robust boundary representation in various applications [31].…”
Section: Boundary Featuresmentioning
confidence: 99%
“…This indicates that boundary features, although not sufficient, could be useful within the context of a nodule classification scheme. Based on the results of previous research which support the utilization of CMP and FD as boundary features [18], [21], [22] this paper investigates their discriminative capability. The utilization of CMP aims to encode large-scale irregularity information as it is the existence of lobes, whereas FD is utilized so as to quantify small-scale irregularity.…”
Section: Boundary Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of CAD for breast cancer, it was shown that shape features that were designed to measure the spiculation of breast masses were important to predicting breast mass malignancy [17][18][19]. Given that mammograms for breast cancer assessment have high resolution compared with the CT scans used for lung nodule assessment, it is important to specifically tackle the issue for the low-resolution case of lung nodules.…”
Section: Introductionmentioning
confidence: 99%
“…The most used descriptors are: circularity, rectangularity [2], compactness(C), spiculation index (SI), fractional concavity (F cc ) [3], fractal dimension [4], Fourier descriptors [5] and statistics based on the distribution of the Normalized Radial Length [6]. One important feature in automated malignity recognition is spiculation level characterization.…”
Section: Introductionmentioning
confidence: 99%